Determination of Magnesium Isotopic Composition of Plant Chlorophylls Based on HPLC and MC-ICP-MS - Zihan AN; Hongyu ZHANG; Jiaxin YIN; Pan ZHANG; Min YAO; Kangjun HUANG (Yankuang ceshi)
The accurate determination of magnesium isotope values of chlorophyll a and chlorophyll b is particularly important for the study of magnesium biosynthesis pathways during chlorophyll formation. HPLC is required before MC-ICP-MS can be utilized, but HPLC lacks a method for separating chlorophylls. Therefore, it is necessary to develop a set of methods for separating plant chlorophyll a and chlorophyll b. The samples separated by this method are suitable for magnesium isotope determination by MC-ICP-MS. Based on the detection wavelength of 665nm and C18 column (7.6mm×250mm, 5μm), the HPLC conditions were optimized by three-factor and three-level orthogonal design to obtain the required parameters. The correlation coefficients of chlorophyll a and chlorophyll b standard curves in the concentration range of 5−50mg/L were greater than 0.9996, the detection limits were 0.40−1.09mg/L, the quantification limits were 1.22−3.31mg/L, the relative standard deviation was less than 8.10%, and the recoveries were 91.92%−111.11%. The magnesium isotope data of the isolated samples also showed that the column temperature of 25℃, flow rate of 1mL/min, and methanol-acetone (80∶20, V/V) mobile phase were reliable as HPLC separation conditions. The method established in this paper provides technical support for the separation of chlorophyll a and chlorophyll b in plants, and the separated samples can be used for magnesium isotope determination. The BRIEF REPORT is available for this paper at http://www.ykcs.ac.cn/en/article/doi/10.15898/j.ykcs.202208300161.